IMPLEMENTASI MEDIASI LITIGASI DI LINGKUNGAN YURISDIKSI PENGADILAN NEGERI PURWOKERTO - Rahadi Wasi Bintoro (Faculty of Law, Universitas Jenderal Soedirman, 2014)
The implementation of mediation in court still seems formalistic. This condition makes the process of a civil case proceed to Supreme Court. Accordingly, the interesting discussion would be the implementation of mediation in jurisdiction of Purwokerto District Court as well as potential factors which likely affect the implementation of mediation in jurisdiction of Purwokerto District Court. This is a sociological juridical research by applying qualitative analysis of which the target population is the judge, mediator and advocate who are selected through purposive sampling. Further, it is analyzed by employing triangulation analysis. The result shows that mediation in the Purwokerto District Court has implemented in accordance with the PerMA No. 1 Year 2008. Legal factors, law enforcement, infrastructure and facility factors have basically contributed to the implementation of mediation in Purwokerto District Court. However, the social factors and cultural factors play an important role in the success of mediation. Key words: mediation, mediator, dispute